The lazy winning project manage : embracing project and personal productivity in an AI empowered world - Taylor, Peter, 1957- (New York, NY : Routledge, 2025)
"Fully updated to reflect developments in AI, remote working, and more, this book brings together two well-loved titles to address emerging trends and challenges in project management and personal development, offering a unique and comprehensive reference book for a new generation of project professionals. In the ever-evolving world of project management, The Lazy Project Manager has been a guiding light for those seeking efficiency through unconventional strategies as well as honesty and a whole lot of fun. With The Lazy Winner, Peter Taylor brought his straightforward and humorous approach to personal productivity and success. Now, Peter has combined these two books to ensure a comprehensive guide for professionals seeking both project management excellence and personal fulfilment - the goal of a great work/life balance. But this book goes beyond evergreen principles, adding rich content on: The effectiveness of the productive lazy approach in harnessing the power of AI, demonstrating that project managers and individuals alike can leverage this hot technology Ways to manage projects remotely and strategies for individuals to thrive in virtual work environments, all using the productive lazy approach New and updated case studies showcasing how the productive lazy approach has been successfully implemented in project management scenarios and personal development journeys The preferences and strengths of the new generations within the workforce, and how the productive lazy approach aligns with their expectations and workstyles Project management professionals worldwide, from new starters learning the ropes to seasoned pros looking for fresh inspiration, will welcome the latest insights and tested strategies from a project management legend"--
Keywords: Project management